TINGKAT PENGETAHUAN MASYARAKAT TENTANG FAKTOR PREDISPOSISI PENYAKIT ASMA DI PUSKESMAS PEMBANTU BERNGAM KOTA BINJAI TAHUN 2020 - Ilham Syahputra Siregar (LPPM Universitas Abdurrab, 2021)
Asthma is a chronic lung disease that often occurs in the world. Data regardingdeaths from asthma have increased in recent decades. According to the GlobalInitiative for Asthma (GINA) in 2008, asthma is defined as a chronic inflammatorydisease of the respiratory tract. Asthma is a chronic airway disease that can be mild,but can persist and interfere with daily activities. Although rarely cause death, thisdisease often causes problems in activities. Researchers conducted a preliminarysurvey which was conducted in January 2020 at the Puskesmas Pembantu BerngamBinjai City, it was found that the prevalence of asthma in the working area of theBerngam Binjai Auxiliary Health Center in 2019 was 42 people. The purpose of thisstudy was to determine the level of public knowledge about the predisposing factorsfor asthma. The type of research is descriptive, the instruments used are interviewsand questionnaires. The data were analyzed in the form of a table for thecharacteristics of the respondent's knowledge and then presented. The results showedthat the majority of people had less knowledge as much as 55%, then goodknowledge was 30%, and sufficient knowledge was 15%